Physical Fitness Levels Of Seluma District 8 State High School Students - Putra, Olda Diansa; Sumantri , Ajis; Astituty , Lina Tri (Journal of Education, 2025)
This research aims to determine the level of physical fitness of male and female students at SMA Negeri 8 Seluma. This research was conducted at SMA Negeri 8 Seluma with a total sample of 44 people, consisting of 22 male students and 22 female students. This research method uses a qualitative descriptive research method. Quantitative descriptive research describes and interprets data relating to situations that are occurring and being experienced now, attitudes and views that are present today, relationships between variables, conflict between two or more conditions, influence on a condition, differences between facts, etc. As a result of data calculations, the average physical fitness results for male students at SMA Negeri 8 Seluma were obtained from 22 people with a score of 16.63 points and included in the medium category. The results of data calculations showed that the average physical fitness of female students at SMA Negeri 8 Seluma was obtained from 22 people with a score of 14 points and was included in the medium category. Based on the results of research and data calculations that have been carried out, it can be concluded that the physical fitness level of male and female students at SMA Negeri 8 Seluma is included in the medium category.